Mass man-made famine of 1921–1923 and issues of Ukrainian grain exports - Baikienich, Dmytro (Ukrainian Peasant, 2021)
Introduction. The article analyzes the statistical data of sown areas, yield, a gross harvest of grain crops of the Ukrainian SSR, RSFSR, and the USSR for the period 1921-1923. The summary information makes it possible to determine the food situation in Ukraine and the level of food supply for its population, observantly track the use of Ukrainian grain for domestic Russian needs, and export abroad, which led to man-made famine. The positions of the representatives of the State Plan set out in the article, prove their conscious decisions on the excessive withdrawal of bread in the Ukrainian provinces, including the starving, to increase the sown area affected by the Holodomor in the Volga regions. The increase in grain exports from the USSR, in particular, due to Ukrainian grain procurements, to restore trade relations with European countries and equalize the trade balance of foreign relations infl uenced the leveling of the themes of mass starvation. Originality. The relevance of the topic chosen for the study is due to the fact that the grain market of Ukraine at the beginning of the twentieth century provided bread not only for the local population but also served as a reserve for other territories of the Russian Empire. At the same time, grain was exported to many European countries. Despite the instability of harvests, there was no massive starvation in Ukraine until the early 1920s. Purpose: the need to investigate regularity in changes in the yield and food situation in the Ukrainian SSR in 1921–1923 in connection with the export of grain to the Russian provinces, which were starving, and abroad. Results. Large areas of grain crops and their harvests in Ukraine played a signifi cant role in international relations at the beginning of the twentieth century and were one of the reasons for the Bolshevik expansion. The combination of natural crop failure with overtime centralized grain procurement, which was used to overcome domestic food problems in Russian provinces and capital cities (red capitals) led to the creation of a food disaster and caused famine in the south of the Ukrainian SSR in 1921 - 1923. The artifi ciality of the famine is confi rmed by unreasonably overstated harvest plans in Ukraine, and then by an increased product tax. A negative factor was the use of Ukrainian grain to restore the sown areas in the affected Volga region, which led to their decrease in the Ukrainian SSR. The deliberate concealment of the situation with the rationed food supply for the population led to the mass mortality expected in the State Planning Committee. The desire of the Soviet authorities to return the USSR to the leaders of the world grain market, as well as to aline the balance of trade and foreign relations through grain exports affected the silence about the situation with famine in the USSR. The signifi cant harvest of 1923 prompted an increase in grain exports and planning for a gradual increase in exports.